2010
DOI: 10.1111/j.1464-410x.2009.09183.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the choice of urinary diversion in patients undergoing radical cystectomy

Abstract: Study Type – Preference (case studies)
Level of Evidence 4 OBJECTIVE To examine the rate at which patients undergo various types of urinary diversion (UD) and the reasons why they had the given reconstruction, analysed in the context of a standardized preoperative protocol for patients undergoing radical cystectomy (RC) at our institution, as there is wide variation in the distribution of patients undergoing continent (CUD) vs incontinent (ICUD) after RC. PATIENTS AND METHODS Between September 2004 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Indeed, in one study, all patients deemed eligible for orthotopic neobladder received standardized preoperative counseling. Of the 149 patients included, only nine selected an incontinent diversion [19]. Additionally, absolute and relative contraindications do exist as shown in Table 1, and these should be explained to the patient [20].…”
Section: Patient Selectionmentioning
confidence: 99%
“…Indeed, in one study, all patients deemed eligible for orthotopic neobladder received standardized preoperative counseling. Of the 149 patients included, only nine selected an incontinent diversion [19]. Additionally, absolute and relative contraindications do exist as shown in Table 1, and these should be explained to the patient [20].…”
Section: Patient Selectionmentioning
confidence: 99%
“…[1][2][3] While the orthotopic neobladder (ONB) most closely resembles the native bladder, continence outcomes are of particular interest to patients and contribute to the choice of urinary diversion made between physician and patient. 4 However, only a few studies, most of which are more than 10 years old, have prospectively reported continence data on these patients, and none are patient-reported based on validated pictorial questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…This bias we believe is minimized given that only 11 patients from the entire cohort underwent an ileal conduit solely based on renal insufficiency and 3 based on surgeon discretion [10].…”
Section: Discussionmentioning
confidence: 99%
“…Indications for cystectomy and urinary diversion included underwent an ileal conduit solely based on renal insufficiency (SCr of > 1.8 mg/dL (159.12 umpl/L)) and 3 based on surgeon discretion due to comorbidities [10]. Looking at all patients undergoing conduit procedures, this group was significantly older than those undergoing continent diversions (71.4 vs 65.3, P < 0.001) and had lower mean preoperative eGFRs (63.8 vs 73.3, P < 0.001).…”
Section: Methodsmentioning
confidence: 99%